Pengaruh Pola Asuh Otoriter, Otoritatif, dan Permisif Terhadap Stres Akademik Pada Remaja - Nathavya Anne Catherine Sinuhaji; Winida Marpaung; Judith Aura Lin; Frans Immanuel Marbun; Alen Tabita Saragih; Putri Andika; Beby Astri Tarigan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Academic stress among adolescents is a growing concern, with parenting style identified as one of its key external determinants. This study examined the effects of authoritarian, authoritative, and permissive parenting styles on academic stress among high school students in Medan. A quantitative approach with a correlational design and multiple linear regression analysis was employed. Participants were 198 students selected from a population of 462 students at Perguruan Buddhis Bodhicitta Medan using disproportionate stratified random sampling. Data were collected using a parenting style scale based on Baumrind's theory and an academic stress scale based on Lazarus and Folkman's theory, both demonstrating adequate validity and reliability. The results showed that parenting styles simultaneously had a significant effect on academic stress (F = 63.020; p < 0.05; Adjusted R² = 0.486). Partially, authoritarian and permissive parenting styles had a positive and significant effect, whereas authoritative parenting showed no significant effect. These findings suggest that controlling and autonomy-restrictive parenting tends to exacerbate adolescent academic stress, while warm and responsive parenting functions as a protective factor. This study underscores the critical role of parenting practices in shaping adolescents coping capacity toward academic demands.